QUALITY OF LIFE AND MULTIPLE SCLEROSIS - REVIEW OF LITERATURE (Fiep Bulletin - online, 2015)
The evaluation of the quality of life (QoL) started to be added in the clinical assays as a third dimension to be evaluated, in view of the necessity to follow the evolution of the illness and its repercussions in well-being of the patient, mainly in chronic illnesses as the Multiple Sclerosis (MS).  The MS is a demyelinating illness that attacks the Central Nervous System.  The illness generally attack young adults at the height of their personal and professional lives, being considered an incapacity illness and therefore brings disastrous consequences in self-esteem and the social-economical capacity of the patients.  The evaluation of the QoL requires multifactorial evaluation and we can observe that in patients with MS some aspects are involved such as: duration of illness, fatigue, depression and physical disorders.  In relation to the general population, patient with MS present significant reduction in the quality of life.  Amongst the most used instruments for gauging QoL in MS, the Sf-36 scale is more widely used followed by the MSQoL-54, that is a specific scale and derivative of the first one.  In relation to the factors that influence the QoL, we can perceive that this patient needs a multiple and  interdisciplinary approach, since the drugs, psychological and physical treatments are directly related to the risk factors for reduction of the QoL.
Keywords: Quality of Life; Multiple Sclerosis and depression.